2009
DOI: 10.1007/s12018-009-9051-9
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Osteoporosis: A Review

Abstract: Glucocorticoid (GC)-induced osteoporosis is the main cause of secondary osteoporosis. Fractures, which are often asymptomatic, can occur in as many as 50% of patients receiving chronic GC therapy. GCs have direct and indirect effects on bone cells (osteoblasts, osteocytes, and osteoclasts) with a suppression of bone formation and an increased bone resorption. The management of patients exposed to GCs should include the use of the minimal effective dose of GC, general health measures, and adequate intakes of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 131 publications
1
41
1
Order By: Relevance
“…These findings, indicating a considerable attenuating effect of TXNIP on OB differentiation and function, are in agreement with the bone formative phenotype observed in active CS, characterized by decreased OB number and function with low levels of biochemical markers of bone formation (3), as well as the rapid increase in bone turnover with increased bone formation, following normalization of cortisol levels. GCs promote the apoptosis of OB and osteocytes in vitro via the activation of caspases (1,19). We found no evidence of decreased apoptosis in silenced TXNIP hFOB, but an increased expression after Dex treatment in caspase 3 and a suppressed expression after silencing TXNIP of caspase 3 and 8 were observed, and supports the possible suppressive effects of TXNIP on OB.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These findings, indicating a considerable attenuating effect of TXNIP on OB differentiation and function, are in agreement with the bone formative phenotype observed in active CS, characterized by decreased OB number and function with low levels of biochemical markers of bone formation (3), as well as the rapid increase in bone turnover with increased bone formation, following normalization of cortisol levels. GCs promote the apoptosis of OB and osteocytes in vitro via the activation of caspases (1,19). We found no evidence of decreased apoptosis in silenced TXNIP hFOB, but an increased expression after Dex treatment in caspase 3 and a suppressed expression after silencing TXNIP of caspase 3 and 8 were observed, and supports the possible suppressive effects of TXNIP on OB.…”
Section: Discussionsupporting
confidence: 66%
“…Hypercortisolism is a well-known cause of bone loss, and patients with endogenous Cushing's syndrome (CS) frequently display low bone mass and fragility fractures. Cortisol excess inhibits bone formation, increases bone resorption, impairs calcium absorption from the gut, and affects the secretion of several hormones, cytokines, and growth factors with potential influence on bone metabolism (1). Sustained and prolonged hypercortisolism leads to a rapid early phase of bone mineral density (BMD) decline due to higher bone resorption, which is followed later by a slower and more progressive phase of impaired bone formation (2).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the bone matrix appears mainly controlled by this "monitoring" cell network and death of osteocytes in a bone territory equals the death of the bone. Tunel staining has been proposed to identify the apoptotic osteocytes [105] and immunohistochemistry with caspase antibodies can also be used [7]. The traumatic section of the osteocyte processes by microcracks or microfractures has been found by block staining with basic fuchsin which stains the cell body and processes [106].…”
Section: Miscellaneous Histological Methodsmentioning
confidence: 99%
“…In addition, a number of studies have reported that, although BMD explains a noticeable number portion of the fracture risk [1,2], there is a large overlap between the BMD values of patients with and without fractures [3][4][5][6]. Furthermore, patients under long-term corticosteroid therapy have an increased risk of fracture than the nontreated osteoporotic patients with the same BMD [7]. Patients with increased bone density in Paget's disease of bone or osteopetrosis can also develop fragility fracture [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoid-induced osteoporosis (GIOP) is the most common cause of secondary osteoporosis (1,2). Patients receiving exogenous glucocorticoids have a rapid increase in the risk of fragility fractures after the initiation of their therapy (3).…”
Section: Introductionmentioning
confidence: 99%